The Rhetorical Structure of Theses and Dissertations in Dentistry: A study in Hispano-America and Spain - Morales, Oscar Alberto; Perdomo, Bexi; Cassany, Daniel; Izarra, Élix (Íkala, Revista de Lenguaje y Cultura, 2020)
Bachelor and master’s thesis or doctoral dissertations play an essential role in scholarship, by spreading research results and strengthening scientific communication. In Iberoamerican universities, these are requisites to get bachelors, masters, and doctor’s degrees in Dentistry. Therefore, there are several proposals to teach this genre to this community. Nonetheless these mostly consist of instructional and prescriptive courses overlooking scientific evidence coming from the disciplinary culture. In the field of discourse analysis, many studies have been conducted on the “thesis” genre in various modalities, disciplines, and languages. However, to date, there are not any research studies on theses or dissertations on Dentistry in the Spanish language. Hence, this article reports on an analysis of the rhetorical structure of 272 Spanish-language theses and dissertations presented in Iberoamerican universities, and published on line between 2000 and 2018. The results show there is no standard format. That is, there are relevant variations in terms of which sections were included and how they were organized. These variations may be associated to the lack of academic writing programs based on real-life practice within Dentistry’s discourse community, among others. Therefore, an evidence-based teaching of academic writing is suggested within the discipline of Dentistry.